On the zero crossings of a generalized shot noise process - Howard, Roy (IEEE, 2011)
Theory and results demonstrate, statistically and by implication, structurally, that the zero crossings of a generalized shot noise process are equivalent to those of a modified random telegraph signal based on grouping of Poisson points. The zero crossings are not statistically consistent with a Poisson point process. © 2011 IEEE.